Комплекс строительной керамики XIV в. из раскопок христианского храма в округе горы Илька - Моисеев, Д.А. (Материалы по археологии, истории и этнографии Таврии, 2014)
Статья посвящена публикации комплекса строительной керамики XIV в., происходящего из раскопок храма на поселении Илька-5 гончарного центра Илька. Храм предварительно был датирован, основываясь на анализе кухонной и столовой керамики, 60-ми гг. XIV - первой половиной XV вв. Благодаря поиску широкого круга аналогий черепице на Мангупском и Эски-Керменском городищах, удалось сузить предварительную хронологию храма на поселении Илька-5 и определить время разрушения церкви на рубеже XIV-XV вв. В статье строительная керамика XIV в. описывается как технологически, так и морфологически. Публикуется большое количество целых форм керамид, хронологию которых, благодаря поиску аналогий на Эски-Кермене и Мангупе, удалось определить в границах одного или двух столетий. The article is devoted to the publication of the complex of building ceramics dating back to the 14th century from the excavations of the church in the settlement of Ilka-5 of the pottery centre of Ilka. The church was preliminary dated back to the 60s of the 14th - the first half of the 15th centuries basing on the analysis of kitchen appliances and table ceramic wares. Owing to the search of analogies to tiles in Mangup and Eski-Kermen city-sites, it became possible to date more exactly the preliminary chronology of the church in the settlement of Ilka-5 and determine the time of the destruction of the church at the turn of the 14th-15th centuries. In the article building ceramics of the 15th century is described technologically and morphologically. A large quantity of whole forms of box tiles is published; the chronology of which was determined within the frame of one or two centuries due to the search of analogies in Eski-Kermen and Mangup.